Fire, volcanism and climate change: the main factors controlling mercury (Hg) accumulation rates in Tropical Lake Lantoa, Sulawesi, Indonesia (~16,500–540cal yr BP) - Nalbant J.; Schneider L.; Hamilton R.; Connor S.; Biester H.; Stuart-Williams H.; Bergal-Kuvikas Olga; Jacobsen G.; Stevenson J. (My University, 2023)
The effects of climate change on long-term mercury (Hg) cycling are still not well understood, as climate changes are usually gradual and can only be assessed using high-resolution archives. Our study site (a small, lowland tectonic lake in Sulawesi, Indonesia) provides a unique opportunity to further understanding of Hg cycling in the Southeast Asian (SEA) tropics during the transition from the Pleistocene to the Holocene, a period of significant climate variability. We present a high-resolution record of Late Glacial and Holocene Hg deposition within the sediments of tropical Lake Lantoa, Sulawesi. Using a multiproxy framework (including pollen, charcoal, carbon:nitrogen ratio and highresolution geochemistry records) we investigate the response of Hg accumulation rates (HgAR) in sediments to shifts in climate between ~16,488 and 538 cal BP. This period encompasses the Bølling-Allerød (BA) warming, Younger Dryas (YD) cooling and Holocene warming events, providing new insights into the effects of global climatic transitions on HgAR in SEA sediments. The Pleistocene Termination had the highest HgAR and substantial variability (µ = 11.32, 5.38–33.91 μg m−2 yr−1), when drier conditions and high charcoal accumulation rates suggest that fire activity was the main source of Hg to the lake.
Keywords: 38.29.03 Методы исследований в стратиграфии